Innovating in public. The introduction of LED lighting in Berlin and Lyon - Nona Schulte-Römer (Technische Universität, 2015)
This dissertation discusses the introduction of LED lighting in urban spaces as an example of innovative public activities. The author conducts a microanalytical investigation into how this globally produced and distributed “disruptive technology” is installed and valorised in specific urban situations. LED pilot projects and demonstrations in cities are considered key innovative activities, as they allow innovators and technology users to present and test new concepts on urban audiences. In light of this, the author argues that the future of technological innovations is not only shaped by technology producers and users, but also urban observers. A series of six ethnographic case studies demonstrate how LED lighting was introduced, further developed and valorised in Berlin and Lyon between 2011 and 2013. The LED projects in both cities differ considerably. The actors in Lyon publically put cutting-edge LED technology to the test, while the Berlin LED installations are reassuringly conventional and exist within the framework of the German capital's familiar cityscape. The six situational analyses demonstrate that these city-specific LED configurations are no coincidence, but the result of socio-material practices and settings. Theoretically, this work draws heavily on the field of science and technology studies (STS) and criticises macroanalytical innovation and diffusion research. A research gap is identified in innovation theory with regard to the conceptualisation of pilot and demonstration projects, that is, public situations in which innovation is recognised and valorised by heterogeneous groups of observers. In this context, the author proposes the notion of the `early public installation' in order to sociologically conceptualise the situation-specific public introduction of new technology as an inherent part of innovation activities. – – Diese Dissertation befasst sich mit der Einführung von LED-Beleuchtung in städtischen Räumen als ein Beispiel für öffentliche Innovationsaktivitäten. Der mikroanalytische Fokus der Arbeit liegt auf der Frage, wie eine weltweit produzierte und vermarktete ,,disruptive Technologie“ situationsspezifisch installiert und bewertet wird. Dabei wird städtischen LED-Pilot- oder Vorzeigeprojekten eine besondere Bedeutung im Innovationsgeschehen beigemessen, weil sie Innovatoren und Techniknutzer_innen erlauben, das Neue öffentlich und vor den Augen städtischer Zuschauer zu testen und zu zeigen. Vor diesem Hintergrund argumentiert die Autorin, dass städtische Beobachter_innen die Zukunft der neuen Technologie mitbestimmen. Entsprechend zeigt sie in sechs ethnografischen Fallstudien, wie LED-Beleuchtung zwischen 2011 und 2013 in Berlin und Lyon eingeführt und stadtspezifisch weiterentwickelt und neu bewertet wurde. Dabei unterscheiden sich die LED-Projekte der beiden Städte grundlegend. Während die Akteure in Lyon den neuesten Stand der LED-Technologie öffentlich auf die Probe stellen, orientieren sich die LED-Lösungen in Berlin an Altbewährten und vertrauten Stadtbild. Wie die sechs ,,Situationsanalysen“ zeigen, sind diese stadtspezifischen LED-Lösungen kein Zufall, sondern das Ergebnis soziomaterieller Praktiken und Gegebenheiten. Theoretisch knüpft die Arbeit insbesondere an Wissenschafts- und Technikstudien (STS) an und kritisiert makroanalytische Innovations- und Diffusionsperspektiven. Die hier identifizierte Forschungslücke betrifft die innovationstheoretische Einordnung von Pilotprojekten und Vorzeigeprojekten, also öffentlichen Situationen, in denen Innovation von heterogenen Beobachter_innen wahrgenommen und bewertet wird. Mit dem Konzept der ,,frühen öffentlichen Installation“ macht die Autorin einen Vorschlag, wie die situationsspezifische Einführung neuer Technologien unter öffentlicher Beobachtung soziologisch als Teil des Innovationsgeschehens verstanden werden kann.
urn:nbn:de:101:1-201804178940; Additional information: Dissertationsschrift / PhD Thesis, Technische Universität Berlin, Fakultät VI – Planen Bauen Umwelt, 2014
Keywords: 300; innovation; diffusion; LED lighting; public experiments; city lights; Innovation; Diffusion; LED Beleuchtung; öffentliche Experimente